PENGARUH NON PERFORMING LOAN (NPL) DAN PERPUTARAN KAS TERHADAP LIKUIDITAS KOPERASI SIMPAN PINJAM SE-KECAMATAN SUKAWATI TAHUN 2017-2020 - Ni Kadek Purnamawati (UNHI Press, 2022)
Liquidity is a ratio that describes the company's ability to meet its short-term obligations. Companies with good liquidity ratios have good liquidity management capabilities. This research was conducted to determine the effect of Non Performing Loans (NPL) and Cash Turnover on Liquidity. The sample in this study is the financial statements of 14 cooperatives in Sukawati District for the period 2017-2020. The data analysis technique used multiple linear regression and hypothesis testing using t-test to test the effect of Non-Performing Loans (NPL) and Cash Turnover on Liquidity. The results of the study stated that there was a negative and significant relationship between Non Performing Loans (NPL) on liquidity, while cash turnover had a significant positive effect on liquidity. Simultaneously Non-Performing Loans (NPL) and cash turnover have an effect on liquidity. The coefficient of determination test shows that 26.1% of the dependent variable is explained by the independent variable, while the remaining 73.9% is explained by other factors or variables.